Analisis Kebutuhan LKPD Penunjang Model PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa - Nurlita Widoarti; Suparman Suparman (Jurnal Inovasi Pendidikan Matematika (JIPM), 2021)
The skills that students must have in solving a problem are mathematical problem solving skills. This is important in the Industrial Revolution 4.0. when students find it difficult to solve HOTS type questions because they still have low problem solving abilities. In the development of thinking patterns, students have very influential problem solving abilities. In the 21st century, what students need is the ability to solve problems. the method used is a qualitative description. Then the object of this research is the teacher and students of MTs Ma'arif Pajaresuk level VIII. The object used is the ability to solve a problem, the learning model and learning resources used by the school. The aim is to analyze the needs of the student worksheet to support the PBL model in improving students' mathematical problem solving abilities. The results obtained in this study are students have low abilities in solving math problems and the media and learning models used have not been able to develop these abilities. so it is necessary to use the PBL model LKPD